Does Freediving Lead to Hippocampal Adaptability to Hypoxia and Maintenance of Episodic Memory? - Julia Micaux; Clément Poiret; Jingwen Zhao; Aya El Hajj; Morgane Tillenon; Abir Troudi Habibi; Franck Mauconduit; Fawzi Boumezbeur; Catherine Chiron; Marion Noulhiane (Journal of Integrative Neuroscience)
Background: Accidental hypoxia has detrimental effects on the brain, particularly on the hippocampal subfields (HS), which are highly sensitive to oxygen deprivation and play a crucial role in episodic memory. This raises the question: could freediving training induce anatomical changes in the HS and lead to significant memory deficits? This study aimed to investigate the impact of a season of freediving training on HS anatomy and episodic memory performance, as freedivers represent a unique natural model for studying the effects of repeated voluntary hypoxic exposure on brain function in healthy individuals. Extending previous research, this study assessed these effects over a prolonged training period. Methods: Seventeen male freedivers were evaluated before and after 7 months of training and compared with a control group of 20 non-freediver athletes. HS anatomical volumes were measured using MRI segmentation and episodic memory performance was evaluated using a pattern separation (PS) task. This task specifically targeted HS-related memory processes by distinguishing between three types of items: (i) identical, (ii) similar, and (iii) new. Results: No significant differences were observed between freedivers and controls in HS volumes or memory performance, either before or after the 7 month training period. A two-way repeated measures ANOVA revealed that freedivers exhibited the same memory pattern as the control group in the PS task. Specifically, both groups performed better with (i) identical items compared with (ii) similar items (p < 0.001) and were less accurate with (ii) similar items compared with (iii) new items (p < 0.001). This aligns with expectations, as distinguishing similar items from previously presented ones is more cognitively demanding than recognizing new items. Conclusions: These findings suggest that repeated voluntary hypoxic exposure during freediving training does not impair episodic memory function. Freedivers’ memory performance remained comparable with that of the control group, with no detectable adverse effects on hippocampal anatomy.